Advancing offline magnetic resonance-guided prostate radiotherapy through dedicated imaging and deep learning-based automatic contouring of targets and neurovascular structures - Schubert, Philipp; May, Matthias; Höfler, Daniel; Fautz, Hans Peter; Hutter, Jana; Merten, Ricarda; Mansoorian, Sina; Weissmann, Thomas; Deloch, Lisa; Schonath, Miriam; Belmas, Natalia; Grabenbauer, Felix; et al. (Physics and Imaging in Radiation Oncology, 2025)
Background and Purpose: Erectile dysfunction (ED) affects quality of life following radiotherapy for prostate cancer. Magnetic resonance imaging (MRI) planning provides superior visualization of potency-related anatomical structures compared to computed tomography (CT), enabling improved sparing. However, contouring these structures in clinical practice is time-intensive and requires expertise. Deep learning (DL) auto-contouring with MRI simulation could make neurovascular-sparing radiotherapy more accessible. Material and Methods: High-resolution 3D T2-weighted SPACE MRI sequences (<1 mm3 resolution) were obtained for 50 patients in treatment position. An expert uro-radiation oncologist contoured erectile function-related anatomy (neurovascular bundles [NVB], pudendal arteries [IPA], penile bulb [PB], corpora cavernosa [CC]) and target structures (prostate [PR], seminal vesicles [SV]). Forty datasets trained and ten tested a 3D nnU-net model. DL-generated contours were geometrically evaluated (surface Dice Score [sDSC], mean surface distance [MSD]) and validated by blinded expert review. Results: DL auto-segmentation achieved an average sDSC of 0.82 (IPA: 0.93, NVB: 0.71, PB: 0.84, CC: 0.90, PR: 0.74; SV: 0.79) and average MSD of 0.74 mm (IPA: 0.61 mm; NVB: 0.88 mm; PB: 0.63 mm; CC: 0.47 mm; PR 0.83 mm; SV: 1.01 mm). Blinded ratings showed no significant differences between DL and expert contours, except for pudendal arteries (Mean DL vs. expert; NVB: 82 vs. 85; PB: 86 vs. 88; CC: 83 vs. 88; PR 81 vs. 83; SV 78 vs. 81 all p > 0.05; IPA: 82 vs. 89; p = 0.028). Conclusion: Combining high-resolution MRI simulation with DL postprocessing enables accurate auto-contouring for MR-guided SBRT planning, potentially advancing neurovascular-sparing radiotherapy beyond current standards.
CRIS-Team Scopus Importer:2025-08-29
Keywords: Auto contouring; Deep learning; MR-guided; Neurovascular structures; Organs at risk; Prostate cancer; Radiotherapy; SBRT

Im Labyrinth dem Ziel entgegen: Doxorubicin/Trabectedin bei Leiomyosarkomen im metastasierten und initial nichtresektablen Stadium - Grabenbauer, Felix; Semrau, Sabine (Strahlentherapie und Onkologie, 2025)
CRIS-Team Scopus Importer:2025-01-31

The Effect of Lurbinectedin as a Monotherapy and in Combination with Ionizing Radiation on Sarcoma Cell Lines - Alsheimer, Hannah; Schiller, Peter; Semrau, Sabine; Grabenbauer, Felix; Fietkau, Rainer; Distel, Luitpold; Hildebrand, Laura (Cancers, 2025)
Background/Objectives: Soft tissue sarcomas are rare, heterogeneous tumors with limited therapeutic options and suboptimal outcomes in advanced stages. Lurbinectedin is a promising new antineoplastic alkylating agent. This study investigates its cytotoxic effects and its potential as a radiosensitizing agent on soft tissue sarcoma. Methods: Four soft tissue sarcoma cell lines were treated with lurbinectedin alone or in combination with ionizing radiation. Single-dose irradiation in a 4-day protocol was compared with prolonged treatment and an additional fractionated ionizing radiation scheme in a 6-day protocol. Cellular responses were analyzed by flow cytometry for apoptosis (Annexin V)/necrosis (7AAD) and cell cycle (Hoechst), clonogenic cell survival, and scratch assays for cell migration. Results: In the 4-day protocol, lurbinectedin induced G2/M arrest in all cell lines (p = 0.029) and significantly increased apoptosis/necrosis (p = 0.029) in SW-872. Lurbinectedin-treatment resulted in a decrease (p ≤ 0.002) of clonogenic cells in all cell lines. In the scratch assay, cell migration was delayed in two cell lines (p = 0.048) after lurbinectedin-treatment. Additional radiotherapy had no significant effect compared to lurbinectedin-monotherapy in apoptosis/necrosis and G/2M arrest in the 4-day protocol, clonogenic cell assay, and scratch assay. In the 6-day protocol, lurbinectedin induced an increase (p = 0.029) in G2/M arrest in all cell lines and apoptosis/necrosis in three cell lines, while resulting in a decrease (p < 0.001) of clonogenic cells. Additional radiotherapy had a significant effect on the decrease in clonogenic cells (p ≤ 0.048) in two cell lines but did not increase G2/M arrest and apoptosis/necrosis. Conclusions: Lurbinectedin had strong effects on three of the selected cell lines by inducing G2/M arrest, promoting apoptosis/necrosis, and reducing clonogenic survival, suggesting that it may be a promising chemotherapeutic agent in soft tissue sarcoma treatment. The effect on the fourth cell line was limited, as well as the effect on cell migration. Single-dose irradiation occasionally interfered with the effects of Lurbinectedin, whereas adding fractionated irradiation caused an additional decrease in clonogenic survival, indicating that the combination of Lurbinectedin with fractionated ionizing radiation may have promising effects.
CRIS-Team Scopus Importer:2025-09-26
Keywords: chemotherapy; clonogenic cell assay; ionizing radiation; lurbinectedin; radiation therapy; radiotherapy; scratch assay; soft tissue sarcoma